Equivalent seminal characteristics in human and stallion at first and second ejaculated fractions. (23rd September 2016) - de la Torre, J.; Sánchez‐Martín, P.; Gosálvez, J.; Crespo, F.
Summary: Sperm quality was assessed in normozoospermic human ( n  = 10) and Spanish breed stallion ( n  = 10) after sperm fractionation during ejaculation. The first ejaculated fraction was separated from the second. A third sample was reconstituted using equivalent proportion of both fractions (RAW). Fraction 1, Fraction 2 and RAW semen were incubated for 30 min at 37°C to homogenise the impact of iatrogenic damage between both species. Sperm concentration, motility and sperm DNA damage were assessed in each fraction and RAW semen. The results showed two important facts: (i) spermatozoa confined at Fraction 1 exhibit superior parameters than those included at Fraction 2 in both species, and (ii) there is a certain level of concordance between species in the proportion of benefit observed when Fraction 1 is compared to RAW semen. Altogether, these results call into question whether the standard practice of whole ejaculate collection can be considered the best strategy when using male gametes for artificial insemination. In fact, the reconstituted RAW semen exhibits poorer semen characteristics than those found in Fraction 1.